Defamiliarisasi dan Bacaan Kontemporer: Telaah Pembacaan Muhammad Shahrûr terhadap Ayat-Ayat Aurat dan Hijâb - Daud, Fathonah K. (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2019)
The thought of interpretation in classical Islamic literature is not final, therefore contemporary issues related to marginalization of women or rules on women’s clothing are among Shahrûr’s concerns. This article examines Muhammad Shahrûr’s reading of the verses of the aurat and hijab. Shahrûr as a contemporary Muslim thinker when studying religious texts tries to provide a different interpretation and contrasts with mufassir in general. Shahrûr’s reading related to the issue of awrah and women’s clothing in studying the verses of the Qur’an using the philosophical approach to language, in the sense that he examines in depth the key words contained in each subject matter, both through paradigmatic and syntagmatic approaches. His method, which aims to counter established thinking and want his readers to understand it as something newly discovered, is called defamiliarization.